2023
DOI: 10.1002/mc.23506
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐like protein 3 promotes colorectal cancer progression and liver metastasis partly via the mitogen‐activated protein kinase 14 pathway

Abstract: Colorectal cancer (CRC) remains one of the most common malignancies worldwide, and liver metastasis represents a considerable challenge during CRC treatment. Aberrant expression of angiopoietin‐like protein 3 (ANGPTL3) has been reported in several human cancer types. However, the function and mechanism of ANGPTL3 in CRC remain unclear. In this study, we first explored ANGPTL3 expression profiles in CRC datasets from ONCOMINE and in local samples from patients with CRC. We then elucidated the function of ANGPTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…ANGPTL3 plays a role in lipid metabolism via the LPL pathway. Previous research has shown a correlation between ANGPTL3 and liver metastasis in CRC [ 33 , 34 ]. Our results suggest that the TG pathways may also contribute to the development of CRC, and ANGPTL3 could be considered an additional chemopreventive target for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL3 plays a role in lipid metabolism via the LPL pathway. Previous research has shown a correlation between ANGPTL3 and liver metastasis in CRC [ 33 , 34 ]. Our results suggest that the TG pathways may also contribute to the development of CRC, and ANGPTL3 could be considered an additional chemopreventive target for CRC.…”
Section: Discussionmentioning
confidence: 99%